Sukuk As Instrument For Increase Indonesian Economy - Siti Ma'sumah; A. Luthfi Hamidi (Wealth: Journal of Islamic Banking and Finance, 2026)
A company that wants to enlarge its efforts can choose an internal bond to get the funding. Corporate bonds play a big role in the development of a company. State Sukuk also has a big role in the economy. With a Sharia-compliant Sukuk, you can finance the development of infrastructure and also become an alternative source of state budget financing. This paper aims to discuss how the role of Sukuk can increase the Indonesian economy, as well as how to optimize the role of Sukuk as a tool to increase the Indonesian economy. The research method used is qualitative with a library approach. The study concludes that the growth of Sukuk in Indonesia is increasing sharply. The rapid growth of Sukuk is not independent of the role of policymakers. The fatwas made by the DSN MUI have given comfort to the public, specifically public Muslims who will invest their funds. The additional capital obtained by the company can be used to open new businesses. With new businesses, new work opportunities will open up for society, thereby increasing public income. The enhancement of public income will increase the purchasing power of society, and the economy will grow. State bonds play an important role in enhancing development. The issuance of State Sukuk with various types of Sukuk series has made a great contribution to the development of various infrastructure projects in Indonesia. The role of investors in the country's economy is not only in the development of physical infrastructure but can also help the government in fulfilling the need for state finances. Sukuk, as an alternative source of financing for the state budget, can be used to close the deficit in the state budget. The benefits of Sukuk are great, as well as the possible profit obtained by attractive investors, regardless of problems in the practice. One problem is the issuance of corporate bonds, which do not yet have a standard structure and uniform contract. To overcome this problem, it is preferable for the MUI as a fatwa holder to become a reference for issuing a fatwa containing information about the standard structure and uniform contract. In this matter, MUI can work with Muslim economists and practitioners who are sukuk investors so that a fatwa can be issued to overcome the problem.